Representation of Love of the Main Characters in the Film Yomei Ichinen no Boku ga, Yomei Hantoshi no Kimi to Datta Hanashi by Director Takahiro Miki - Nur Hastuti; Yustina Martlyne; Wikan, Johana (Jurnal Sastra Indonesia, 2025)
This study examines the representation of love between the main characters, Akito and Haruna, in the film Yomei Ichinen no Boku ga, Yomei Hantoshi no Kimi to Datta Hanashi, also known as Drawing Closer. Directed by Takahiro Miki in 2024, this research employs a qualitative descriptive method and a literary psychology approach. It utilizes a note-taking technique to analyze character dialogues and classify data according to Robert J. Sternberg's Triangular Theory of Love. The goal is to explore the forms of love exhibited by Akito towards Haruna and to delve into the underlying values of their relationship from a literary psychology perspective, focusing on the components of intimacy, passion, and commitment as outlined by Sternberg. The findings reveal that the main character, particularly Akito, embodies two components of love, illustrated through nine key elements reflecting intimacy and commitment in his attitudes and behaviors towards Haruna. This analysis ultimately identifies the theme of friendship and love, highlighting its significance in understanding relational dynamics in contemporary narratives.